Komunikasi Informasi Edukasi Keluarga Berencana Berbantuan Multimedia untuk Pemilihan Alat Kontrasepsi - Eka Nur Rahayu; C. Asri Budiningsih; B.M. Wara Kushartati (Sekolah Tinggi Ilmu Kesehatan AKBIDYO, 2021)
Service quality and Educational Information Communication (IEC) can affect the continuity of contraceptive use. The purpose of this study is how the effectiveness of multimedia-assisted KIE Family Planning (KB) by midwives in assisting the selection of contraceptives for pregnant women. The pre-experimental research design was in the form of a one group pretest-posttest design, namely looking at the knowledge of pregnant women about family planning before and after IEC and knowing the selection of contraceptives before and after IEC which was carried out at the Larashati Sewon Clinic. The sample of this study was 41 pregnant women in the third trimester of pregnancy with the technique of taking acidental sampling. The instrument used was a questionnaire. Data analysis using nonparametric test two samples related test with Wilcoxon. There was a difference in the choice of contraceptive before and after being given IEC. There is a difference in the knowledge of pregnant women before and after being given IEC. IEC services for family planning by midwives for patients using multimedia can increase knowledge, so that it can help pregnant women to choose contraceptives after childbirth.Keywords: Educational information communication, family planning, contraceptive selection